IMPROVING LEARNING OUTCOMES OF CLASS II MI AL KAUTSAR STUDENTS USING JARIMATICS METHODS IN LESSONS MULTIPLICATION MATHEMATICS IN 2023/2024 - Rabiah Adawiyah; Muhammad Ali Akbar (MERDEKA : Jurnal Ilmiah Multidisiplin, 2023)
Rabiah Adawiyah NIM. 858412777, IMPROVING STUDENTS' MATHEMATICS LEARNING OUTCOMES ON MULTIPLICATION MATERIAL USING THE MATHEMATICS METHOD IN CLASS II MI AL KAUTSAR ACADEMIC YEAR 2023/2024. The low skills think creative students ' eyes lesson mathematics material multiplication class II MI Al Kautsar background back study This . Based on results interview with the class II teacher that learning mathematics during This seldom using learning media as tool help Study . So that researcher do repair learning with using concrete media . Study This own objective to : 1) know How use method Jarimatika to improve creative thinking skills on Multiplication material in IIMIS Al- Kautsar class. know How enhancement Skills think creative material Multiplication number round student class II MIS Al Kautsar use finger method .